2014
DOI: 10.20870/productions-animales.2014.27.2.3064
|View full text |Cite
|
Sign up to set email alerts
|

Changements et innovations dans les systèmes d’élevage en Afrique

Abstract: En Afrique, les productions animales font face à une évolution importante de la demande et sont en proie à de multiples changements. Les systèmes d’élevage du futur devront être à la fois plus productifs et respectueux de l’environnement et pour cela les éleveurs devront innover. Aujourd’hui les systèmes agro-pastoraux deviennent majoritaires, le pastoralisme se maintient notamment dans les zones arides, et les élevages périurbains et spécialisés prennent de l’importance. Les changements locaux et globaux surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In sub-Saharan Africa, several practices are implemented by cattle farmers to manage the herd [ 13 , 14 ]. In Benin, Idrissou et al [ 15 ] identified three cattle farming types according to their practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sub-Saharan Africa, several practices are implemented by cattle farmers to manage the herd [ 13 , 14 ]. In Benin, Idrissou et al [ 15 ] identified three cattle farming types according to their practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, these are not the only livestock farming systems encountered in Africa. Nowadays, sedentary systems are becoming numerous [ 13 ]. It would therefore be appropriate to consider them in such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in both Europe and Africa, farmers are changing their farms, notably by implementing innovations having different origins, such as farmers, professional groups, technical support systems, policies (Ingrand et al, 2014). Vall et al (2014) described changes and innovations in Burkinese livestock systems receiving technical support (government dairies, milk powder taxation) that encouraged breeders to use crossbreeding and artificial insemination, and to produce forage and purchase feed in the dry season. The sociotechnical regime in which agriculture finds itself makes alternative innovations difficult, although they do exist (Stassart et al, 2012).…”
Section: Introductionmentioning
confidence: 99%